Virtual reality as a platform for research in gambling behaviour. (June 2020) - Dickinson, Patrick; Gerling, Kathrin; Wilson, Liam; Parke, Adrian
Abstract: Research into gambling behaviour is an important aspect of mitigating the effects of problem gambling. However, the majority of existing studies are conducted in the laboratory, rather than in vivo, raising questions over the generalisability of results. Virtual reality (VR) is well established as an effective tool for exposure therapy, and has also been used in other experimental contexts: such work is often motivated by the ability of the platform to create ecologically valid conditions, and simulations that would be hard to create in real life. Whilst a small number of studies have used VR to evoke the urge to gamble, and also to conduct behavioural studies, no work has yet considered the differences in experience between laboratory and VR conditions. We approach this from the perspective of immersion, arousal and user experience, and conduct a within-subjects study (N = 48) in which participants play a gambling game both on a laptop in a laboratory, and on a virtual gaming machine located in a VR simulation of a betting shop. Our results show that participants reported higher levels of arousal, as well as higher levels of immersion in the game when playing in VR. There was also a significant difference in self-reported physical task workload in VR. Based on our results, we argue for further use of VR in experimental research related to gambling, as well as further study of the experience and responses of problem gamblers to VR simulations of real-world gambling. Highlights: Gambling experience in virtual reality was compared to that in the laboratory. Higher levels of immersion and arousal were reported playing in virtual reality. Participants also experienced higher physical task workload in virtual reality. Virtual reality simulations may be beneficial for the study of gambling behaviour.